2006
DOI: 10.1080/09546630600727115
|View full text |Cite
|
Sign up to set email alerts
|

A single centre, open‐label, cross‐over study of pharmacokinetics comparing topical zinc/clindamycin gel (Zindaclin®) and topical clindamycin lotion (Dalacin® T) in subjects with mild to moderate acne

Abstract: Zinc/clindamycin gel (Zindaclin 1%) gel, is a new once-daily topical acne treatment (Strakan Ltd) containing clindamycin phosphate equivalent to 1% clindamycin and zinc acetate in a formulation, which leads to a reduced systemic absorption of clindamycin through the skin. The objective of the study was to compare the systemic absorption of clindamycin from zinc/clindamycin gel and clindamycin lotion (Dalacin T topical lotion, Pharmacia Ltd) after repeated twice-daily topical administration for two periods of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…In a 5-day crossover study of clindamycin 1% lotion and zinc/clindamycin 1% gel, median clindamycin peak plasma concentrations were reduced by 41% on day 1 and 34% on day 5, and areas under the plasma concentration-time curve were reduced by 49% on day 1 and 36% on day 5 with the zinc-containing formulation (all p < 0.05). Similar findings were noted with trough plasma concentration and urinary excretion data [46] . Topical clindamycin does not alter the systemic bioavailability of concurrent tretinoin [42] .…”
Section: Pharmacokineticssupporting
confidence: 85%
“…In a 5-day crossover study of clindamycin 1% lotion and zinc/clindamycin 1% gel, median clindamycin peak plasma concentrations were reduced by 41% on day 1 and 34% on day 5, and areas under the plasma concentration-time curve were reduced by 49% on day 1 and 36% on day 5 with the zinc-containing formulation (all p < 0.05). Similar findings were noted with trough plasma concentration and urinary excretion data [46] . Topical clindamycin does not alter the systemic bioavailability of concurrent tretinoin [42] .…”
Section: Pharmacokineticssupporting
confidence: 85%
“…This study clearly reveals that CLDMP has a potent capacity to scavenge hydroxyl radical directly, but not superoxide anion. Although the generation of reactive oxygen species (ROS) through myeloperoxidase and NADPH oxidase (NADPH, reduced nicotinamide adenine dinucleotide phosphate) by phagocytic cells, such as neutrophils, is known to be an important host defense mechanism directed towards the killing of invading microorganisms, 17,18 ROS have potential deleterious effects on the biological system, as they can damage proteins, lipids, and nucleic acids 5–7 . In the case of NADPH oxidase, superoxide anions are generated, and the dismutation of superoxide anion then generates hydrogen peroxide, which gives rise to hydroxyl radical formation through a Fenton‐type reaction 19–22 .…”
Section: Resultsmentioning
confidence: 99%
“…It is available as CLDM hydrochloride for oral administration in capsules, as CLDM phosphate (CLDMP) for intramuscular or intravenous injection, and as CLDM palmitate for oral suspension 3 . In addition to intramuscular or intravenous injection, CLDMP is the most widely used topical antibacterial agent for acne treatment because of its proven safety and efficacy in many clinical studies 4–7 . Recently, it has been reported that CLDM has anti‐inflammatory properties, such that it reduces tumor necrosis factor‐α (TNF‐α) concentration in lipopolysaccharide (LPS)‐stimulated THP‐1 cells, and decreases serum TNF‐α and interleukin‐1β (IL‐1β) concentrations and increases serum IL‐6 concentrations in the mouse model 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…That which can be provided by stable isotope studies includes: Data demonstrating the maximal plasma/serum zinc concentration obtained relative to dose (which relates to optimal absorption of zinc using zinc stable isotope kinetics), duration of effect and timing of the doses. These data can be provided using zinc stable isotope techniques [ 158 , 159 , 160 , 161 ]. Delivery of zinc to the target tissue as informed by the volume of distribution, by plasma protein binding and, if needed, tissue biopsy assays.…”
Section: Discussionmentioning
confidence: 99%
“…Data demonstrating the maximal plasma/serum zinc concentration obtained relative to dose (which relates to optimal absorption of zinc using zinc stable isotope kinetics), duration of effect and timing of the doses. These data can be provided using zinc stable isotope techniques [ 158 , 159 , 160 , 161 ].…”
Section: Discussionmentioning
confidence: 99%